THE PATTERN OF ADEQUATE HOUSING RIGHTS FULFILLMENT IN INDONESIA - Madalina, Maria; Purwadi, Hari; Firdausy, Adriana Grahani; ., Achmad (Faculty of Law, Universitas Sebelas Maret, 2018)
The fulfillment of adequate housing is the part of the fulfillment of human rights as stated in the constitution. The state can not ignore and have to do it when he has the ability to comply the adequate housing for poor people. Adequate housing is more than material it is correlated with the human existence, hence it is categorized as human rights. As part of human rights, the fulfillment of this adequate housing is need to be respect, comply, and protect either by the state and society. The state need to take part to the fulfillment of adequate housing for those who can not afford it. As the state have the capability to realize the adequate housing for the poor, they can not ignore the human rights unfulfillment. This research focused on law guarantee recognition and the pattern of the adequate housing fulfillment in Indonesia. It is revealed that the pattern is correlated with the state political law which is the policy in the form of laws and local regulation that decided the direction, purpose, and the law substance in housing. Beside its society, the policy also need the private sector involvement, as a result the fulfillment of the adequate housing rights has to be done by the three party.